Biological and medicinal properties of grapes and their bioactive constituents: An update - Yadav, M.; Jain, S.; Bhardwaj, A.; Nagpal, R.; Puniya, M.; Tomar, R.; Singh, V.; Singh, V.; Prasad, G.B.K.S.; Marotta, F.; Yadav, H.
The grape is one of the most valued conventional fruits, worldwide. Although most of the parts of the grapevine are useful, primarily, the grape is considered as a source of unique natural products not only for the development of valuable medicines against a number of diseases, but also for manufacturing various industrial products. Over the last few decades, apart from the chemistry of grape compounds, considerable progress has been made towards exploring the biological activities of various grape-derived constituents. Today, it is well established that in addition to serving as food, the grape is a major source of several phytochemicals. The main biologically active and well-characterized constituent from the grape is resveratrol, which is known for various medicinal properties in human diseases. This review discusses the roles of various grape-derived phytochemicals in relation to various diseases. © Copyright 2009, Mary Ann Liebert, Inc. and Korean Society of Food Science and Nutrition.
Keywords: 3,4 DIHYDROXYSTILBENE; 4 HYDROXYSTILBENE; 4,4' DIHYDROXYSTILBENE; ALEANILIC ACID; ANTHOCYANIN; CATECHIN; DIETHYLSTILBESTROL; DIPRIM; EPICATECHIN; EPIGALLOCATECHIN GALLATE; FLAVONOID; GALLIC ACID; MELANIN; OLEANOLIC ACID; OLIGONO; OLIGONO; PINOSYLVIN; PLANT MEDICINAL PRODUCT; PROANTHOCYANIDIN DERIVATIVE; RESVERATROL; STILBENE DERIVATIVE; TANNIN DERIVATIVE; UNCLASSIFIED DRUG